PENGARUH PENAMBAHAN DAUN PEPAYA TERFERMENTASI DALAM RANSUM TERHADAP ORGAN DALAM ITIK BALI - N. K., Wiliyanti; Siti, N. W.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2017)
This study was to determine the effect of fermented papaya leafs in the ration to internal organs bali female ducks. Duck been used were 45 bali female ducks. The design used was randomized completely design, which consists of three treatment and five replication so there are 15 experimental units, each treatment used three bali female duck. Three treatments such as of A (control ration not containing fermented papaya leafs), B (ration containing 5% fermented papaya leafs), C (ration containing 10% fermented papaya leafs). Variables observed were liver, heart, gall bladder, spleen, gizzard, small intestine and large intestine. The results showed that the addition of fermented papaya leaf in the ration given significant effect (P<0,05) to liver weight, heart weight, length small intestine and length large intestine bali female duck and given not significant affect (P>0,05) to spleen, gaal bladder, and gizzard weight bali female duck. The result of study showed that treatments 5% has significant affect to internal organs. Internal organs such as heart weight, length small intestine and length large intestine have higher weight than control. Treatments 10%, on the other hand, only affect heart and liver weight compare to control. In addition to those, this study also found that both treatments (5% and 10%) not influence gizzard, spleen and gaal bladder weight.
Keywords: internal organs, female bali duck, fermented papaya leaf